2012
DOI: 10.1007/s00404-012-2403-6
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy body mass index and gestational weight gain with the outcome of pregnancy: a 13-year study of 292,568 cases in China

Abstract: Being overweight/obese and having a high weight gain, as well as being underweight and having a low weight gain, were associated with increased risks for adverse pregnancy outcomes in Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
91
3
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 19 publications
22
91
3
11
Order By: Relevance
“…Another study reported favourable gestational outcomes in obese women who gained less than 5 kg in weight over the course of pregnancy as compared to those who gained more than 5 kg (25). A large study on pregnant women in China followed over a 13 year period has also reported higher maternal and fetal adverse outcomes with excess gestational weight gain, as well as low birth weight following insufficient weight gain in pregnancy (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported favourable gestational outcomes in obese women who gained less than 5 kg in weight over the course of pregnancy as compared to those who gained more than 5 kg (25). A large study on pregnant women in China followed over a 13 year period has also reported higher maternal and fetal adverse outcomes with excess gestational weight gain, as well as low birth weight following insufficient weight gain in pregnancy (26).…”
Section: Discussionmentioning
confidence: 99%
“…Low pre-pregnancy body mass index (BMI) is a significant risk factor for delivering low-birth weight (LBW) infants [1,2]. Gestational weight gain (GWG) and gestational week at delivery (GWD) are also crucial for preventing the delivery of LBW infants [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…. , If allowed to give dietary guidance according to the patient's preferences, but must maintain a balanced nutrition, to ensure adequate daily food intake, and enhance the patient's body resistance [8].…”
Section: Clinical Data and Methodsmentioning
confidence: 99%